From restrictive to more liberal: variations in mortality among patients in opioid maintenance treatment over a 12-year period - Anne Bukten; Marianne Riksheim Stavseth; Thomas Clasuen (BMC, 2019)
Abstract Background As the effect of opioid maintenance treatment (OMT) on overdose mortality varies both between and within countries, treatment programs need to be evaluated in different treatment settings and over time within settings. We evaluated variations in mortality in a national programme: from the initial rollout as restrictive and low-capacity to its gradual change into more liberal and higher-volume. Methods A 12-year prospective longitudinal cohort study including all persons (n = 6871) applying for and entering OMT in Norway (1997-2009). We followed all patients until 2009 or until death. We used crude mortality rates (CMR) to calculate overdose and all-cause mortality among patients in OMT before, during and after treatment, during a 12-year time-period. We also calculated variations in overdose and all-cause mortality over the course of treatment and after treatment termination. We fitted proportional hazards models with covariates to the data. Results OMT significantly reduces risk of mortality compared to being outside of treatment. The reduction in overdose death was most substantial during the initial phase of the Norwegian OMT-programme, still; we consistently find that overdose deaths were more than halved in all calendar-periods throughout observation. We did not find an elevated risk of overdose death in the first weeks of treatment, nor in the first weeks after treatment cessation. Conclusion In Norway, OMT reduces overall mortality. Reduction in mortality is likely dependent of both treatment delivery and characteristics of the at-risk population.